ANALISIS KESESUAIAN SURAH AL-MULK DALAM BUKU SURAT YASIN TERHADAP MUSHAF STANDAR INDONESIA (MSI) - Tiasagita, Tiasagita; Irsyadi, Najib; Yuspa, Anida (STIT Darul Hijrah Martapura, 2025)
AbstractThis study aims to analyze the conformity of the writing of Surah Al-Mulk in a Surat Yasin booklet published by CV. Al Baba with the Indonesian Standard Mushaf (Mushaf Standar Indonesia/MSI), particularly in terms of rasm, ḍabṭ, and waqf signs. This research employs a library research method with a qualitative descriptive approach. The research data consist of the text of Surah Al-Mulk contained in the Surat Yasin booklet, which is examined through documentation study and directly compared with the text of Surah Al-Mulk in the Indonesian Standard Mushaf as the primary reference. Data analysis is conducted using a comparative method based on the principles of Uthmani rasm, ḍabṭ, and waqf–ibtidā’. The results show that the writing of Surah Al-Mulk in the examined booklet does not fully conform to the Indonesian Standard Mushaf. Out of 30 verses, 14 verses (approximately 47%) exhibit discrepancies, particularly in the writing of yā’ sākinah without dots and the use of waqf signs that differ from MSI standards. These discrepancies demonstrate recurring patterns and indicate the absence of an official tashih (verification) process in popular religious publications. Therefore, this study emphasizes the importance of strengthening mushaf verification mechanisms and enhancing mushaf literacy in the publication of religious books in Indonesia. AbstrakPenelitian ini bertujuan untuk menganalisis kesesuaian penulisan Surah Al-Mulk dalam buku Surat Yasin terbitan CV. Al Baba dengan Mushaf Standar Indonesia (MSI), khususnya pada aspek rasm, ḍabṭ, dan tanda waqaf. Penelitian ini menggunakan metode penelitian kepustakaan (library research) dengan pendekatan kualitatif-deskriptif. Data penelitian berupa teks Surah Al-Mulk dalam buku Surat Yasin yang dianalisis melalui studi dokumentasi dan dibandingkan secara langsung dengan teks Surah Al-Mulk dalam Mushaf Standar Indonesia sebagai rujukan utama. Analisis data dilakukan dengan metode komparatif berdasarkan kaidah rasm ‘Utsmānī, ḍabṭ, dan waqf–ibtidā’. Hasil penelitian menunjukkan bahwa Surah Al-Mulk dalam buku Surat Yasin tersebut tidak sepenuhnya sesuai dengan Mushaf Standar Indonesia. Dari total 30 ayat, ditemukan 14 ayat (±47%) yang mengandung ketidaksesuaian, terutama pada penulisan huruf yā’ sukun tanpa titik serta penggunaan tanda waqaf yang berbeda dari standar MSI. Ketidaksesuaian ini menunjukkan pola berulang dan mengindikasikan lemahnya proses pentashihan pada buku keagamaan populer. Penelitian ini menegaskan pentingnya perluasan pengawasan pentashihan mushaf dan peningkatan literasi mushaf dalam penerbitan buku-buku keagamaan di Indonesia.